Estado centralizado e descentralizado: alterações morfológicas nas áreas antigas da cidade do Porto/Portugal - Moreira, Bruno Miguel Fernandes (2017)
The production and appropriation of the city and its organization in space is largely the result of the action of private agents who have distinct strategies, ideologies and modus operandi, which are often contradictory and conflict generating. For this production, appropriation and organization to be verified, it becomes, then, a compatibility model between the agent models. This compatibilization action / repression occurs implicitly and explicitly through the State, the public agent who holds the national / international legitimacy and the instruments available to do so. However, as relations between the state and the several private agents are not uniform with no time and space, undergoing updates to each historical period and variations in distinct geographical locations. In the sense of deepening the knowledge on this vast subject, in the present research a comparative analysis of the State interference was made, in its centralized structure and its descriptive structure of governance, about the mechanisms historically used to articulate the consolidated city with its expansion areas. With the intention of overcome the problem of abstract and generalizing conclusions, a case study was chosen: The Historic Center of the City of Oporto and its adjacent areas defined as Priority Intervention Zones located at N.W of Portugal. To obtain a less fragmented vision of that specific reality, it was fallen back upon a diachronic analysis of the several phases of governance of the modern Portuguese nation- State between the years of 1763 and 2016. Crossing the synthesis of the main characteristics of each governance phase (Absolutist, Monarchical Liberal, Republican Liberal, Authoritarian, Democratic) with the morphological changes that occurred in the urban fabric of Oporto, it was interesting to verify that: the implementation of a decentralized structure of organization/ administration of power didn’t come to introduce a drastic rupture in the guidelines and in the production methods and appropriation of the old city. On the contrary, it came to maintain the cyclical alternation among the periods in that the urban space is dominated by the market forces, and the periods in that the State uses the image of the city as a propaganda instrument and social control.